Verbal Fluency: Language or Executive Function Measure?. Issue 1 (2nd January 2016) - Whiteside, Douglas M.; Kealey, Tammy; Semla, Matthew; Luu, Hien; Rice, Linda; Basso, Michael R.; Roper, Brad
Abstract : Measures of phonemic and semantic verbal fluency, such as FAS and Animal Fluency (Benton, Hamsher, & Sivan, 1989), are often thought to be measures of executive functioning (EF). However, some studies (Henry & Crawford, 2004a, 2004b, 2004c ) have noted there is also a language component to these tasks. The current exploratory factor-analytic study examined the underlying cognitive structure of verbal fluency. Participants were administered language and EF measures, including the Controlled Oral Word Association Test (FAS version), Animal Fluency, Boston Naming Test (BNT), Vocabulary (Wechsler Adult Intelligence Scale-III), Wisconsin Card-Sorting Test (WCST, perseverative responses), and Trail-Making Test-Part B (TMT-B). A 2-factor solution was found with the 1st factor, language, having significant loadings for BNT and Vocabulary, while the second factor was labeled EF because of significant loading from the WCST and TMT-B. Surprisingly, FAS and Animal Fluency loaded exclusively on to the language factor and not EF. The current results do not exclude EF as a determinant of verbal fluency, but they do suggest that language processing is the critical component for this task, even without significant aphasic symptoms. Thus, the results indicated that both letter (phonemic) and category (semantic) fluency are related to language, but the relationship to EF is not supported by the results.